Utilização da torta de girassol (Helianthus annus) na alimentação de cabras mestiças - Costa, Amanda Modesto (Universidade Federal Rural do Semi-Árido, 2014)
Food supplementation is essential for providing adequate demand for energy and nutrients such as carbohydrates and protein that meets the needs for maintenance and production of the animals. The co-products of biodiesel are presented as viable alternative to supply fiber, energy and protein in the diet of ruminants. This study aimed to evaluate the effect of increasing levels of sunflower cake (Helianthus annuus) in feeding lactating goats. Total of 25 crossbred goats Anglo Nubian and Savannah housed in 5 bays with 5 bays. The statistical design was randomized block design (RBD) with five treatments (0%, 15%, 30%, 45% and 60%) of sunflower cake inclusion. Were evaluated nutrient intake, production and composition of milk and some economic aspects. Samples of the food provided, as well as the remains were heavy and taken to Animal Nutrition Laboratory (Lana) to determine the chemical composition. The evaluation of milk yield were obtained by the method of daily milk control for chemical physical analysis of milk samples was collected monthly. For simple financial analysis was determined to gross margin, rate of return and leveling point. Statistical analysis was performed using the statistical software SAS version 9.1 (SAS 1997). Tukey test was used for parametric data. With regard to the production and composition of milk is observed that there was no statistical difference between treatments, but no increase in the production of milk treatment had 60% of sunflower cake inclusion in the others. It was found that the sunflower cake can replace soybean meal to the level of 60%, treatment with 60% inclusion showed higher milk production, fat, lactose, protein and total solids, in grams / day as well as having presented higher gross margin, better rate of return and it was the only treatment that has reached the leveling point
Use of sunflower cake (Helianthus annuus) in Power crossbred goats
Keywords: Goats; Consumption of milk; Animal nutrition; Costs; Sunflower; Cabras; Consumo do leite; Nutrição animal; Custos; Girassol; CIENCIAS AGRARIAS::ZOOTECNIA